Giving rituximab in patients with occult or resolved hepatitis B virus infection: are the current guidelines good enough?. (June 2015) - Civan, Jesse; Hann, Hie Won
<x xml:space="preserve">Abstract</x> Introduction: Hepatitis B virus (HBV) reactivation after 'resolved' infection can occur in the setting of immunosuppression, including iatrogenically induced by anti-CD20 antibodies. The presence of antibodies against the HBV core antigen (anti-HBc) is a marker of risk for this phenomenon. The risk of this occurring in patients with circulating HBV surface antigen (HBsAg) is well characterized, but is less well characterized in patients who are HBsAg negative. Areas covered: This article reviews the literature regarding HBV reactivation in the context of rituximab therapy. We have limited our review to HBsAg-negative patients, and clinical outcomes following HBV reactivation. Expert opinion: We have recommended prophylactic anti-viral therapy for all HBsAg-negative/anti-HBc-positive patients undergoing rituximab therapy in combination with other immunosuppressive therapy.